EKSISTENSI TUKANG BECAK DITENGAH DOMINASI OJEK ONLINE DI KOTA PALANGKA RAYA - Yuseva Yuseva; Anisa Pebrianti; Iman Irawansyah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
Traditional modes of transportation such as becaks are part of the informal economy and have long facilitated the movement of people in cities across Indonesia. This study aims to examine the presence of becak drivers amidst the rise of app-based transportation and the strategies they employ to survive in Palangka Raya. The study employs a qualitative descriptive approach, with data collected through interviews, field observations, and documentation. Informants were selected using purposive sampling, while data analysis was conducted using the interactive model by Miles and Huberman. This study employs James C. Scott’s “Survival Mechanisms” theoretical framework, which encompasses three strategies: leveraging social networks, seeking alternative income sources, and adhering to the principle of “cost-saving.” The findings reveal that the presence of online ride-hailing services significantly impacts the economic conditions of becak drivers. This results in low and unstable daily incomes. In response, they seek other jobs, change their operating locations, and wait for passengers without a clear plan. Although their numbers have decreased, pedicab drivers remain because they play an important social role around traditional markets.